Mutations mark cell lineages and sectors in flowers of a woody angiosperm. - Yilun Ji; Xiaonan Chen; Xiaohui Zhang; Wenjing Wang; Lan Xue; Yifan Zhong; Dacheng Tian; Sihai Yang; Long Wang; Milton Brian Traw; Ju Huang (PLoS Genetics)
While radial sectors of flowers are likely to accumulate nested mutations, the distribution of natural somatic mutations across floral organs in dicot plants has not been studied previously. Here, we use next generation sequencing of 78 independent genome samples through sepals, petals, stamens, and carpel of two flowers to ask 1) whether radial sectors accumulate nested mutations, 2) whether carpels share de novo mutations with the radial parts, and 3) whether mutations can be used to estimate founder cell numbers in the floral anlagen. Mutations described seven sectors, each including a single petal and adjacent sepals, consistent with radial cell proliferation in the floral cup that predates the split of the sepal and petal cell populations. Mutations nested into two deep cell lineages that propagated through branching events and into every floral organ and unit of both flowers. Both carpels possessed two flower-wide de novo mutations, confirming that their genetic origin does not precede the floral anlagen. However, carpels possessed none of the sector marking mutations and therefore isolated genetically early in floral bud formation. Cell estimates of the flower-wide point mutations were most consistent with two cell floral initiation, one L1 and one L2, suggest a model of cell division in the floral anlagen. These observations represent the first genome-wide map of natural mutation distributions in a radially symmetric angiosperm flower.